COLD MIXTURE OF INORGANIC BINDER: STATUS AND PROSPECTS OF DEVELOPMENT (INORGANIC VS. ORGANIC) - S. S. Tkachenko; G. A. Kolodiy; L. G. Znamensky; A. A. Ermolenko (Литьë и металлургия)
The technologies of molding from cold-hardening mixtures based on organic resins and inorganic metal phosphate binders are compared. The use of the latter is preferable for a number of technological indicators. Also, without additional investments, the problem of labor and environmental protection is completely solved.